WORK - LIFE BALANCE AND ENGAGEMENT AS PARAMETERS ON MILLENNIAL TEACHERS’ WORK PERFORMANCE - Juliana; Johan (Dinasti International Journal of Management Science, 2020)
The purpose of this research is to analyze the effects of work – life balance and employee engagement on the millennial teachers’ work performance in Jakarta area. The data collection was being collected by having questionnaires sent to 100 millennial teachers who work in formal and informal educational institutions. This research used a quantitative method and SmartPLS 3.2.7 software was being used to evaluate the outer and inner model. The results indicate that there is a negative significant effect of work – life balance on the teachers’ work performance and there is no effect of employee engagement on work performance.